Determinants of the saving behaviour among students of UiTM Terengganu / Dilla Kartini Naradin ... [et al.] - Naradin, Dilla Kartini; Ismail, Fathiyah; Harun, Nur Syikri; Khamis, Zaleha (2017)
This research seeks to investigate the saving behaviour among the students of Universiti Teknologi Mara (UiTM) Terengganu. This study used the primary data. The data were collected by using the personally administered questionnaires online and offline. The sample consisted of 267 students out of the target population of the study; the UiTM Terengganu bachelor's degree students. The convenience sampling method was used in collecting the data and the results were generated by using the Statistical Package for Social Science (SPSS) statistic 20 for Windows. The Pearson Correlation and Multiple Linear Regression analyses were employed to identify whether or not the three independent variables (IVs) have the relationships with the saving behaviour of the UiTM Terengganu students. The findings reported that Financial Literacy (FL), Financial Management (FM), and Financial Socialisation (FS) have positive relationships with the Saving Behaviour (SB) while the FL has the strongest impact on SB among the three IVs.